Analysis of Landslide-Prone Areas Using the Microtremor Method in the Mandeh Region, South Coast of West Sumatra - Della Putri (Department of Physics, Universitas Negeri Padang, 2026)
Landslides are the downward movement of masses of soil and rock caused by slope instability. The instability develops when the balance of forces acting on the slope is disturbed. Mandeh area is one of the areas frequently affected by landslides. Based on these issues, mitigation efforts are needed to minimize losses due to landslides, which can be identified using the Microtremor method based on dominant frequency, amplification, and the seismic susceptibility index. The collected microtremor data were processed using the Horizontal to Vertical Spectral Ratio (HVSR) method to obtain dominant frequency, amplification factor, shear wave velocity, and seismic vulnerability index values, which were then used to assess landslide susceptibility in the study area, with data collection conducted directly in the study area. Landslide-prone areas in the Mandeh area, Koto XI Tarusan District, were identified as areas with dominant frequencies of 0.1 Hz – 3.85 Hz, amplification factors of 3.41, 3.67, 4.78 and 5.331, shear wave velocities of 120 m/s – 170 m/s, and seismic vulnerability indexes of 3.17537–5.456896. The areas that meet these criteria are located at research points TP2, TP7, T11 and TP14.